The rate of regeneration of mangrove ecosystems on post-bauxite mining areas in the waters of Sei Carang, Tanjungpinang City - Moza Fani Maylani; Febrianti Lestari; Susiana Susiana (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2022)
The mangrove ecosystem in the Sei Carang estuary waters, Tanjungpinang city is a mangrove ecosystem that has land conversion activities and leaves the environment with open land. The purpose of this study was to determine the density and regeneration rate of mangrove ecosystems on post-bauxite mining areas as seen from seedling, sapling, and trees. This research was conducted in July-October 2022. This study was conducted at four stations determined by the purposive sampling method, based on the existence of a mangrove ecosystem in which there are post-bauxite mine openings in the Sei Carang estuary waters, Tanjungpinang City. For each station, 3 plots of data were collected, with a plot size of 1x1m for the seedling category, a plot of 5x5m for sampling and a plot of 10x10m for trees. Data analysis used the formula for species density, for the regeneration rate by comparing the data from the calculation of the density of seedling, sapling and trees and then the formula for the diversity index. The results of the study found eight types of mangroves, namely Rhizophora apiculata, Rhizophora mucronata, Bruguiera gymnorhiza, Soneratia alba, Avicennia lanata, Nypa fruticans, and Lumnitzera litorea. Density values at station 1 for seedling 40,000 individual/Ha, sapling 2,667 individual/Ha, and trees 1,533 individual/Ha, at station 2 for seedling 30,000 individual/Ha, sapling 1,467 individual/Ha, and trees 500 individual/Ha, at station 3 for seedling 36,667 individual/Ha, sapling 5,200 individual/Ha, and trees 1,600 individual/Ha then at station 4 for seedling 53,333 individual/Ha, sapling 3,200 individual/Ha, and trees 2,133 individual/Ha. The level of mangrove regeneration at all observation stations is quite good.